2020
DOI: 10.1002/ange.201913231
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Biofunctionality of Metal–Organic‐Framework‐Encapsulated Enzymes through Controllable Embedding Patterns

Abstract: Embedding an enzyme within a MOF as exoskeleton (enzyme@MOF) offers new opportunities to improve the inherent fragile nature of the enzyme, but also to impart novel biofunctionality to the MOF. Despite the remarkable stability achieved for MOF‐embedded enzymes, embedding patterns and conversion of the enzymatic biofunctionality after entrapment by a MOF have only received limited attention. Herein, we reveal how embedding patterns affect the bioactivity of an enzyme encapsulated in ZIF‐8. The enzyme@MOF can ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Other works suggest that the Zn 2+ :linker:enzyme ratios and the total precursor concentration are important parameters that determine the phase and the morphol- The role of proteins in the material formation process has been the subject of controversy. Some authors reported a biomimetic mineralization approach that utilizes biomacromolecules (proteins) as crystallization and directing agents for controlling crystal morphology of ZIF-8 [77,79,81,106]. However, Cui et al demonstrated that the crystal morphology of ZIFs is primarily dependent on the concentrations of 2-methylimidazole and Zn 2+ ions instead of the biomacromolecules (proteins) [76], as other authors had confirmed [81,106].…”
Section: Zifs the Most Widely Studied Mofs As A One-pot Support For B...mentioning
confidence: 99%
“…Other works suggest that the Zn 2+ :linker:enzyme ratios and the total precursor concentration are important parameters that determine the phase and the morphol- The role of proteins in the material formation process has been the subject of controversy. Some authors reported a biomimetic mineralization approach that utilizes biomacromolecules (proteins) as crystallization and directing agents for controlling crystal morphology of ZIF-8 [77,79,81,106]. However, Cui et al demonstrated that the crystal morphology of ZIFs is primarily dependent on the concentrations of 2-methylimidazole and Zn 2+ ions instead of the biomacromolecules (proteins) [76], as other authors had confirmed [81,106].…”
Section: Zifs the Most Widely Studied Mofs As A One-pot Support For B...mentioning
confidence: 99%
“…23,24 Furthermore, some studies have shown that long time immersion of enzymes with MOF precursors might cause the activity loss increasingly. 25 Nevertheless, the fabricated MOF configurations, related to aperture scale and substrate size, can notably impact the bioactive level of the encapsulated enzymes and limit their applicabilities. 26 More appropriate nanoscaled aperture MOFs, which can be quickly formed under biofriendly conditions, are therefore urgently to be devised to broaden their strategic applications in the next generation of de novo enzyme@MOF biocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…These robust mechanical frameworks protect the enzymes from harsh conditions such as denaturants and organic solvents. Recently, our lab has reported the successful encapsulation of enzymes in single ZIF-90 crystals, one of a zeolitic imidazolate framework family, by using a de novo mild water-based approach. Meanwhile, it was demonstrated that the efficacy of enzyme@MOF hybrid materials in preserving the catalytic function of the encapsulated enzymes under size-sheltering protection and reticular crystalline confinement effects against proteolytic proteins and denaturing agents, respectively. However, the merits of the de novo methods via water-based synthesis have only been demonstrated for certain MOF materials, for example, microporous ZIF-type MOFs such as ZIF-90 or ZIF-8, which can be synthesized under biocompatible aqueous conditions, have been used for enzyme encapsulation. , Furthermore, some studies have shown that long time immersion of enzymes with MOF precursors might cause the activity loss increasingly . Nevertheless, the fabricated MOF configurations, related to aperture scale and substrate size, can notably impact the bioactive level of the encapsulated enzymes and limit their applicabilities .…”
Section: Introductionmentioning
confidence: 99%
“…163 Ouyang and co-workers immobilized glucose oxidase (GOx) and CytC in ZIF-8 MOF, from MOF precursors. 164 They found that GOx in ZIF-8 retained a similar activity to the free enzyme, whereas Cyt C retained only 10% activity. The study revealed that the enzyme type and enzyme nucleation ability influenced the activity of the enzyme within the MOF.…”
Section: Metal-organic Frameworkmentioning
confidence: 96%